Early Chinese heritage language learning in Canada: A study of Mandarin- and Cantonese-speaking children's receptive vocabulary attainment. (December 2021) - Li, Guofang; Gunderson, Lee; Sun, Zhuo; Lin, Zhen
Abstract: Chinese immigrant children in North America often experience rapid growth in their English lexicon, while their heritage language (HL) vocabulary development is characterized by early stabilization and decline. This study was designed to explore whether and how factors such as SES, gender, L1, immigration status, home language use, mainstream and HL school attendance have influenced Mandarin- and Cantonese-speaking first graders' ( N  = 76) early HL vocabulary development in Canada. Students' HL receptive vocabulary was measured by the Chinese Peabody Vocabulary Test (C-PPVT-R) and home and school information was collected through the Alberta Language Environment Questionnaire (ALEQ). Statistical analyses revealed significant differences in the effects of L1 and gender between Mandarin- and Cantonese-speaking first graders. Mandarin-speaking girls outperformed Mandarin-speaking boys and their Cantonese-speaking peers. Family SES was found to be a significant factor affecting early HL vocabulary development. While Mandarin-speaking students' performance was associated with the richness of their home language environments, Cantonese-speaking students' performance was not. Group performance was not significantly associated with home language use. Findings suggest the need to move beyond a usage-based theory to understand better home interactions across L1 and SES subgroups that shape differential performances.